The Gospel and Henry VIII : evangelicals in the early English Reformation - Ryrie, Alec (Cambridge studies in early modern British history., 2003)
The last years of Henry VIII's life, 1539-47, have conventionally been seen as a time when the king persecuted Protestants. This book argues that Henry's policies were much more ambiguous; that he continued to give support to Protestantism and that many accordingly also remained loyal to him. It also examines why the Protestants eventually adopted a more radical, oppositional stance, and argues that English Protestantism's eventual identity was determined during these years.